Diazoxide preconditioning of endothelial progenitor cells improves their ability to repair the infarcted myocardium. (7th July 2015) - Mehmood, Azra; Ali, Muhammad; Khan, Shaheen N.; Riazuddin, Sheikh
Abstract Reduced survival and homing of the transplanted cells in the oxidative stressed ischemic environment limits the potential outcome of cell therapies for myocardial ischemia. Diazoxide (DZ), a highly selective mitochondrial ATP sensitive K+ channel opener, is known to improve the survival and therapeutic ability of mesenchymal stem cells and skeletal myoblasts for the repair of heart failure. The current study explored the effect of DZ preconditioning in improving the ability of endothelial progenitor cells (EPCs) to counteract, in vitro oxidative stress, and to repair the infarcted myocardium. The EPCs were preconditioned by 30 min incubation with 200 μM DZ followed by exposure to 200 μM hydrogen peroxide (H2O2) for 2 h. Non‐preconditioned EPCs with and without exposure to H2O2 were used as control. DZ preconditioning of EPCs resulted in significantly reduced cell injury as shown by reduced lactate dehydrogenase release and expression of annexin V‐PE in comparison to untreated EPCs. Furthermore, DZ preconditioned EPCs exhibited upregulated expression of prosurvival genes (VEGF, SDF‐1α, PCNA, and Bcl2), improved chemokines release (VEGF, IGF, and SDF‐1α), viability, Akt phosphorylation and tube formation. In vivo experiments involved transplantation of DZ preconditioned and untreated EPCs in the left ventricle after permanent ligation of left anterior descending coronary artery in rats. The results demonstrated that DZ EPCs transplanted group showed significant reduction in infarct size along with robust cell proliferation, angiogenesis and improvement in cardiac function. The current study demonstrates that DZ preconditioning enhances EPCs survival under oxidative stress in vitro and their ability to treat myocardial infarction.